Investigation the Entrepreneurship Characteristics of Sports Education Students - Özhan Bavli; Ali Coskun (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The aim of this study is to examine the entrepreneurship levels of students from different departments who receive sports education. Design/methodology/approach:Random 155 university students who were voluntarily participated in the study. University students entrepreneurship scale was used to collect data. SPSS program used for analysis. Findings: The total entrepreneurship score was found as 133.1±11.3 points. No significant difference was found between the genders. There was a significant difference was found between the departments. It was found that the average scores of the students of the recreation department were significantly lower than the average scores of the students of the other departments (p:0.036). Research limitations/implications: Based on the study findings; It can be said that entrepreneurship scores are generally high, but it may be beneficial to provide entrepreneurship-themed trainings to students in order to reduce the difference between departments. Paper type: Research paper